Electrochemical synthesis of poly(3-aminophenylboronic acid) in ethylene glycol without exogenous protons. Issue 15 (23rd March 2016) - Wang, Feifan; Zou, Feixue; Yu, Xinxin; Feng, Zhenyu; Du, Na; Zhong, Yaohua; Huang, Xirong
Abstract : In ethylene glycol the electropolymerization of 3-aminophenylboronic acid can been realized without exogenous hybridization agent and protons. Abstract : A non-aqueous solution of tetra- n -butylammonium fluoride (TBAF) in ethylene glycol has been tried for the first time as a supporting electrolyte for the electropolymerization of 3-aminophenylboronic acid (APBA). Unlike the traditional acidic aqueous solution, the present medium needs no exogenous protons; moreover, the presence of CF3 COOH is found to be unfavorable for the polymerization. The protons are in situ generated by the reaction between the boronic acid group on APBA and 1, 2-dihydroxyl on ethylene glycol. So, ethylene glycol serves as not only the solvent but also the proton source. As a part of the supporting electrolyte, F − is found to be involved in the electrochemical synthesis of poly(3-aminophenylboronic acid) (PAPBA), but it is not indispensable. Studies on the electropolymerization process indicate that the size of the ions in the electrolyte affects the rate of the doping/dedoping process. The smaller the cation, the easier the doping/dedoping process, and the better the stability of the grown film. As demonstrated by Fourier transform infrared spectra, UV-vis spectra, and scanning electron microscopy, the obtained PAPBA is a cross-linked nanoporous polymer membrane that has a good adherence to the glassy carbon electrode.